The introduction of average speed over distance cameras as a road safety tool to reduce excessive speeds and accidents on the roads of the Western Cape, South Africa - Van Velden, Wouter (Stellenbosch : Stellenbosch University, 2017)
Thesis (MScEng)--Stellenbosch University, 2017.